The analysis of Task Based Learning in improving the pronunciation of the English language learner - I Gede Nika Wirawan (Universitas Bali Dwipa, 2022)
Pronunciation is one of the key aspects in which area the students must improve in the university. One person can communicate to the other in a language when they can understand each other and if they can understand each other it means that they have a very good pronunciation especially for English it is not very easy to pronounce some words for some speaker especially for the Indonesian speaker it is not very easy to pronounce all of the English words because the Indonesian language is very different with the English language. That is why pronunciation is one of the lesson that must be taught in the class because not all of the Indonesian people can pronounce the English words correctly they need more practice do you pronounce the words because the Exxon of the Indonesian people are very strong and they need a lot of practice at home or in the classroom with the teachers to practice work to improve their pronunciation. This is very important especially if they want to communicate with the native speaker especially for the English native speaker and they will not understand what the people say unless we pronounce the word correctly. And to pronounce the word correctly needs a lot of practices not just in the classroom but also practices at home.